Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites